2022
DOI: 10.1186/s12877-022-03258-2
|View full text |Cite
|
Sign up to set email alerts
|

Therapy options for those affected by a long lie after a fall: a scoping review

Abstract: Background After a fall, more than half of older people living alone are unable to get up or get help independently. Fall-related recumbency makes affected individuals aware of functional status limitations and increased vulnerability. Patient-centered therapy is needed to manage physical, psychological, and social needs. This review summarizes the current evidence on care options for the special patient population. Methods The scoping review used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…A preliminary search of the Cochrane Database of Systematic Reviews did not yield any current or in-progress reviews on the characteristics of a long lie. One review on the treatment of long lie was identified, but this focused mainly on the consequences of a long lie and the resulting therapy and prevention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary search of the Cochrane Database of Systematic Reviews did not yield any current or in-progress reviews on the characteristics of a long lie. One review on the treatment of long lie was identified, but this focused mainly on the consequences of a long lie and the resulting therapy and prevention [ 13 ].…”
Section: Introductionmentioning
confidence: 99%